Monitoring amphibians in a changing climate: conservation assessment of Natterjack Toad Epidalea calamita using ecoacoustics - Carlos Abrahams; David Pickett; Sandrina Finocchio-Daniels; Alex Bush (Journal for Nature Conservation, 2026)

An evaluation of transcriptomic points of departure and gene expression profiles for larval fathead minnows (Pimephales promelas) exposed to 22 chemicals with known modes of action - Camille G. Baettig; Jenna E. Cavallin; Kendra Bush; Alex Kasparek; Peter Schumann; Kevin Flynn; Daniel L. Villeneuve (Aquatic Toxicology, 2026)

Predicting plant community change using satellite remote sensing in the Greater Cape Floristic Region - Andrew C. Slater; Nelmarie Saayman; Helga van der Merwe; Liesl Vorster; Ian R. Hartley; Alex Bush (South African Journal of Botany, 2025)

Conservation planning for environmental water to climate refugia in the manageable Murray–Darling Basin - Joanne M. Bennett; Simon Linke; Shane Brooks; Alex Bush; James Hitchcock; Carmel Pollino; Ross M. Thompson (Journal of Environmental Management, 2025)

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Precipitation variability and environmental change across late Quaternary glacial-interglacial cycles in lowland Central America: Insights from Lake Petén Itzá (Guatemala) sediments - Rodrigo Martínez-Abarca; Liseth Pérez; Thorsten Bauersachs; Frederik Schenk; Steffen Kutterolf; Mark Brenner; Thomas Guilderson; Alex Correa-Metrio; Flavio S. Anselmetti; Robert Brown; Daniel Ariztegui; Laura Macario-González; et al. (Quaternary Science Reviews, 2024)

Systematic nature positive markets - Alex Bush; Katherine Hannah Simpson; Nick Hanley (Conservation Biology, 2024)
Environmental markets are a rapidly emerging tool to mobilize private funding to incentivize landholders to undertake more sustainable land management. How units of biodiversity in these markets are measured and subsequently traded creates key challenges ecologically and economically because it determines whether environmental markets can deliver net gains in biodiversity and efficiently lower the costs of conservation. We developed and tested a metric for such markets based on the well‐established principle of irreplaceability from systematic conservation planning. Irreplaceability as a metric avoids the limitations of like‐for‐like trading and allows one to capture the multidimensional nature of ecosystems (e.g., habitats, species, ecosystem functioning) and simultaneously achieve cost‐effective, land‐manager‐led investments in conservation. Using an integrated ecological modeling approach, we tested whether using irreplaceability as a metric is more ecologically and economically beneficial than the simpler biodiversity offset metrics typically used in net gain and no‐net‐loss policies. Using irreplaceability ensured no net loss, or even net gain, of biodiversity depending on the targets chosen. Other metrics did not provide the same assurances and, depending on the flexibility with which biodiversity targets can be achieved, and how they overlap with development pressure, were less efficient. Irreplaceability reduced the costs of offsetting to developers and the costs of ecological restoration to society. Integrating economic data and systematic conservation planning approaches would therefore assure land managers they were being fairly rewarded for the opportunity costs of conservation and transparently incentivize the most ecologically and economically efficient investments in nature recovery.

Novel community data in ecology-properties and prospects - Florian Hartig; Nerea Abrego; Alex Bush; Jonathan M. Chase; Gurutzeta Guillera-Arroita; Mathew A. Leibold; Otso Ovaskainen; Loïc Pellissier; Maximilian Pichler; Giovanni Poggiato; Laura Pollock; Sara Si-Moussi; et al. (Trends in Ecology & Evolution, 2024)

Warming, drought, and disturbances lead to shifts in functional composition: A millennial‐scale analysis for Amazonian and Andean sites - Masha T. van der Sande; Mark B. Bush; Christine M. Åkesson; Juan Carlos Berrio; Alex Correia Metrio; Suzette G. A. Flantua; Henry Hooghiemstra; S. Yoshi Maezumi; Crystal N. H. McMichael; Encarni Montoya; Nicole A. S. Mosblech; Majoi de Novaes Nascimento; et al. (Global Change Biology, 2023)
Tropical forests are changing in composition and productivity, probably in response to changes in climate and disturbances. The responses to these multiple environmental drivers, and the mechanisms underlying the changes, remain largely unknown. Here, we use a functional trait approach on timescales of 10,000 years to assess how climate and disturbances influence the community‐mean adult height, leaf area, seed mass, and wood density for eight lowland and highland forest landscapes. To do so, we combine data of eight fossil pollen records with functional traits and proxies for climate (temperature, precipitation, and El Niño frequency) and disturbances (fire and general disturbances). We found that temperature and disturbances were the most important drivers of changes in functional composition. Increased water availability (high precipitation and low El Niño frequency) generally led to more acquisitive trait composition (large leaves and soft wood). In lowland forests, warmer climates decreased community‐mean height probably because of increased water stress, whereas in highland forests warmer climates increased height probably because of upslope migration of taller species. Disturbance increased the abundance of acquisitive, disturbance‐adapted taxa with small seeds for quick colonization of disturbed sites, large leaves for light capture, and soft wood to attain fast height growth. Fire had weak effects on lowland forests but led to more stress‐adapted taxa that are tall with fast life cycles and small seeds that can quickly colonize burned sites. Site‐specific analyses were largely in line with cross‐site analyses, except for varying site‐level effects of El Niño frequency and fire activity, possibly because regional patterns in El Niño are not a good predictor of local changes, and charcoal abundances do not reflect fire intensity or severity. With future global changes, tropical Amazonian and Andean forests may transition toward shorter, drought‐ and disturbance‐adapted forests in the lowlands but taller forests in the highlands.

‘Small Data’ for big insights in ecology - Lindsay C. Todman; Alex Bush; Amelia S.C. Hood (Trends in Ecology & Evolution, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Prenatal exposure to polycyclic aromatic hydrocarbons is not associated with behavior problems in preschool and early school-aged children: A prospective multi-cohort study - Erin R. Wallace; Erin Buth; Adam A. Szpiro; Yu Ni; Christine T. Loftus; Erin Masterson; Drew B. Day; Bob Z. Sun; Alexis Sullivan; Emily Barrett; Ruby HN. Nguyen; Morgan Robinson; et al. (Environmental Research, 2023)

Modern pollen assemblages of the Neotropics - Mark B. Bush; Alex Correa‐Metrio; Robert van Woesik; Aaron Collins; Jennifer Hanselman; Pablo Martinez; Crystal N. H. McMichael (Journal of Biogeography, 2021)
Aim Modern pollen assemblages provide a means to calibrate fossil pollen data and to provide a translation from habitat and vegetation type to pollen representation. Here we provide a database of modern pollen abundances from a broad range of neotropical habitats and locations. Location The Neotropics, especially western Amazonia, the Andes, The Galápagos, Central America, Puerto Rico and Mexico. Taxon Angiosperms and Gymnosperms Methods Over a 30‐year period, mud–water interface samples, moss polsters, soils and pollen traps were used to assay modern pollen assemblages. Standard extraction methods were used, and a minimum of 300 terrestrial pollen grains were counted and identified in each sample. Bioclimatic data were assigned to each location, and sexual traits and pollination syndromes are provided for some genera. A detrended correspondence analysis (DCA) shows the structuring of the data relative to mean annual temperatures (MAT), mean annual precipitation (MAP) and precipitation of the driest quarter (PDQ). Probability density functions of distances among samples are calculated within and between Holdridge Life Zones, based on sample DCA scores. Results The modern pollen of 636 locations are documented, with >500 pollen types identified. The dataset spans settings with MAT 25°C, and with MAP ranging from c. 500 to 5,000 mm, and PDQ from 80 to 1,500 mm. Ordination of the dataset provides evidence that assemblages differ according to temperature and precipitation, although historical biogeography also shapes pollen rains. The pollen grains of zoophilous species contribute important information to habitat descriptions, but they are under‐represented in the dataset. Main conclusions The dataset covers a broad environmental range and can help inform biogeographical and palaeoenvironmental interpretation of palaeoecological records. Some caution in using the data is needed as the field of tropical palynology is maturing and the data gathered 30 years ago are less detailed than those gathered recently. Although anemophilous taxa tend to be over‐represented in neotropical pollen spectra, the majority of pollen identified in each sample are from zoophilous species.

Incorporating existing thermal tolerance into projections of compositional turnover under climate change - Alex Bush; Renee Catullo; Karel Mokany; Tom Harwood; Andrew J. Hoskins; Simon Ferrier (Global Ecology and Biogeography, 2019)
Aim Observed, realized niche space often underestimates species’ physiological tolerances due to interactions with other species, dispersal constraints, and because some combinations of influential environmental factors do not currently exist in the real world. Conversely, correlative ecological niche models rely on the assumption that the range of environmental conditions encompassed by a species’ geographic distribution accurately reflects their environmental tolerances, including community‐level approaches like generalized dissimilarity modelling (GDM). We extend GDM to better understand what effect broader environmental tolerances could have on compositional turnover under climate change. Innovation We show how GDM can be adjusted as a function of best‐available estimates of the average ratio between realized and potential niche widths to modify projected temporal turnover. We demonstrate this approach by using the estimated niche ratios of Australian plant species ( n = 7,184) relative to thermal extremes, and the rate at which this ratio varied with temperature. The modified GDMs showed existing thermal tolerance could reduce the turnover predicted by standard models under climate change by up to 11%. We further show how the reduction in expected turnover by 2090 will influence where a greater proportion of the current community will persist in a region. Main conclusions We suggest that standard spatial GDMs and their modified versions represent the extremes of ecological niche perspectives (i.e., realized and potential) and the range of tolerance communities may have when responding to environmental change. GDM projections therefore identify the range of uncertainty associated with a critical model assumption, and as climate change continues, ongoing community monitoring could be used to validate the balance between the two possibilities.

Truncation of thermal tolerance niches among Australian plants - Alex Bush; Renee A. Catullo; Karel Mokany; Andrew H. Thornhill; Joseph T. Miller; Simon Ferrier (Global Ecology and Biogeography, 2018)
Aim Despite recognition that realized distributions inherently underestimate species' physiological tolerances, we are yet to identify the extent of these differences within diverse taxonomic groups. The degree to which species could tolerate environmental conditions outside their observed distributions may have a significant impact on the perceived extinction risk in ecological models. More information on this potential error is required to improve our confidence in management strategies. Location Australia. Time Period 1983–2012. Major Taxa Studied Plants. Methods To quantify the scale and spatial patterns of this disparity, we estimated the existing tolerance to thermal extremes of 7,124 Australian plants, more than one‐third of the native continental flora, using data from cultivated records at 128 botanical gardens and nurseries. Hierarchical Bayesian beta regression was used to assess whether factors such as realized niches, traits or phylogeny could predict the incidence or magnitude of niche truncation (underestimation of thermal tolerances), while controlling for sources of collection bias. Results Approximately half of the cultivated species analysed could tolerate temperature extremes beyond those experienced in their native range. Niche truncation was predictable from the breadth and extremes of their realized niches and by traits such as plant growth form. Phylogenetic relationships with niche truncation were weak and appeared more suited to predicting thermal tolerances directly. Main conclusions This study highlights a widespread disparity between realized and potential thermal limits that may have significant implications for species' capacity to persist in situ with a changing climate. Identifying whether thermal niche truncation is the result of biotic interactions, dispersal constraints or other environmental factors could provide significant insight into community assembly at macroecological scales. Estimating niche truncation may help to explain why certain ecological communities are more resilient to change and may potentially improve the reliability of model projections under climate change.

Incorporating evolutionary adaptation in species distribution modelling reduces projected vulnerability to climate change - Alex Bush; Karel Mokany; Renee Catullo; Ary Hoffmann; Vanessa Kellermann; Carla Sgrò; Shane McEvey; Simon Ferrier (Ecology Letters, 2016)
Based on the sensitivity of species to ongoing climate change, and numerous challenges they face tracking suitable conditions, there is growing interest in species' capacity to adapt to climatic stress. Here, we develop and apply a new generic modelling approach ( AdaptR ) that incorporates adaptive capacity through physiological limits, phenotypic plasticity, evolutionary adaptation and dispersal into a species distribution modelling framework. Using AdaptR to predict change in the distribution of 17 species of Australian fruit flies (Drosophilidae), we show that accounting for adaptive capacity reduces projected range losses by up to 33% by 2105. We identify where local adaptation is likely to occur and apply sensitivity analyses to identify the critical factors of interest when parameters are uncertain. Our study suggests some species could be less vulnerable than previously thought, and indicates that spatiotemporal adaptive models could help improve management interventions that support increased species' resilience to climate change.

Holocene changes of Andean alder ( Alnus acuminata ) in highland Ecuador and Peru - Chengyu Weng; Mark B. Bush; Alex J. Chepstow‐Lusty (Journal of Quaternary Science, 2004)
Fossil pollen records from the high Andes of Ecuador and northern Peru show that Alnus increased in abundance at most sites following warming associated with the onset of the Holocene. The peak of Alnus pollen abundance occurred between ∼9000 and 5000 yr BP. However, between 6500 and 4500 yr BP, the abundance of Alnus pollen declined markedly in all of the available records, including sites both within and above its modern distribution range. Even though the beginning of this decline may have been time‐transgressive, the greatest reduction of Alnus abundance is consistent between sites, occurring at ca. 4500 yr BP. This synchrony suggests that one or more factors affected Alnus populations across the whole region. A cooler climate, droughts and anthropogenic activity are discussed as possible causes on such a large spatial scale. A scenario is suggested in which the early–mid Holocene increase in Alnus populations was curtailed by droughts, and then further impacted by major regional cooling from ca. 5000 yr BP onwards. Human agricultural activities in this wetter interval may also have delayed Alnus recovery. A resurgence of Alnus populations at 2000–1000 yr BP may have been a response to regional warming coupled with human land management practices. Copyright © 2004 John Wiley & Sons, Ltd.

A late Holocene record of arid events from the Cuzco region, Peru - Alex Chepstow‐Lusty; Michael R. Frogley; Brian S. Bauer; Mark. B. Bush; Alfredo Tupayachi Herrera (Journal of Quaternary Science, 2003)
The small recently infilled lake basin of Marcacocha (13°13′S, 72°12′W, 3355 m) in the Cuzco region of Peru has a morphology and location that renders it extremely sensitive to environmental change. A record of vegetation, human impact and climatic change during the past 4200 yr has been obtained from a highly organic core taken from the centre of the basin. Sustained arid episodes that affected the Peruvian Andes may be detectable using the proxy indicator of sedge (Cyperaceae) pollen abundances. As the lake‐level was lowered during sustained drier conditions, the local catchment was colonised by Cyperaceae, whereas during lake floods, they retreated or were submerged and pollen production was correspondingly reduced. Drier episodes during prehistoric times occurred around 900 bc , 500 bc , ad 100 and ad 550, with a longer dry episode occurring from ad 900 to 1800. Evidence from the independently derived Quelccaya ice‐core record and the archaeological chronology for the Cuzco region appears to support the climatic inferences derived from the sedge data. Many of these aridity episodes appear to correspond with important cultural changes in the Cuzco region and elsewhere in the Central Andes. Copyright © 2003 John Wiley & Sons, Ltd.